Role of peroxisomes in physiology and pathology of ossification and bone metabolism - Qian, Guofeng; Justus Liebig University Giessen (My University, 2010)
Only sparse information is available in the literature on peroxisomes and theirenzyme composition in different cell types of the mouse skeleton. However, thevital importance of peroxisomes in these tissues is accentuated by the strongossification defects and growth retardation observed in children with peroxisomalbiogenesis defects, such as the Zellweger syndrome, or corresponding knockout(KO) mouse models. Therefore, in the first part of this dissertation theperoxisomal compartment was characterized in different cell types of cartilageand bone, using a variety of morphological, biochemical as well as molecularbiological techniques. In the second part of this dissertation, the pathologicalconsequences of peroxisome dysfunction and the molecular pathogenesis ofossification defects were examined in PEX11beta KO mice, a mouse model forZellweger syndrome.The results of this thesis revealed the presence of peroxisomes in all distinctcell types of the skeleton, however, with significant differences in their numericalabundance and enzyme composition. The peroxisomal biogenesis protein Pex14pproved to be the best marker for identification of the whole peroxisomalpopulation in different cell types. The peroxisomal metabolic proteins catalaseand the lipid transporter ABCD3 were strongly enriched in hypertrophicchondrocytes and osteoblasts, suggesting a close relationship of these proteinsto ossification processes. In primary cell cultures, a low numerical abundance ofperoxisomes was noted in 3d osteoblasts, whereas a constantly higherabundance of peroxisomes was observed in more mature osteoblasts at latertime points (7d, 11d and 15d). In contrast, the protein levels of catalase and 3-ketoacyl-CoA thiolase, which were also low in 3d osteoblast reached theirmaximum at 7 days and declined thereafter. Interestingly, different members ofthe PPAR-family (peroxisome proliferation-activated receptors alpha, beta;, gamma,transcription factors regulating peroxisomal beta-oxidation genes, were altered inan individual pattern during osteoblast differentiation. PPARalpha was regulated in asimilar pattern as the peroxisomal metabolic proteins, whereas the expression ofPPARgamma mRNA exhibited opposite regulation and the one for PPARbeta was notaltered at all. Activation of PPARalpha by treatment of primary osteoblasts withciprofibrate for 6 days increased both peroxisomal number and metabolicenzymes, whereas treatment with the PPARgamma agonist troglitazone altered theexpressions of peroxisomal metabolic enzymes without a significant change inperoxisomal numerical abundance. Interestingly, thiolase and ABCD3 weredifferentially regulated by PPARalpha or PPARgamma agonists, indicating that differentPPARs might indeed have distinct effects on the regulation of peroxisomal genes.Analyses of PEX11beta KO mice with flat-panel volumetric computer tomographyor skeletal stainings revealed a strong reduction of bone volume, mass anddensity in comparison to their wildtype littermates. Comparative analyses ofskeletal tissues and primary osteoblast cultures showed a significant decrease inthe synthesis of osteoblast secretory marker proteins and a severe retardation indifferent ossification processes. Furthermore, increased oxidative stress andsevere alterations of bone specific signaling pathways were detected in PEX11betaKO osteoblasts. An increase in PPARgamma was observed, which was accompanied bya decrease in canonical Wnt signaling and FoxO1 protein expression. In addition,the osteoblast transcription factor Runx2 was relocalized from the nucleus intothe cytoplasm. All above mentioned alterations might contribute to theossification defects observed in peroxisomal disorders.Taken together, the results of this dissertation indicate that regularperoxisomal metabolic functions are required for intramembranous andendochondral ossification processes through protecting osteoblasts against ROSand lipid toxicity as well as the control of PPAR ligand homeostasis.

Zum Thema Peroxisomen und Enzymzusammensetzung dieser Organellen imStützgewebe sind aus der Literatur kaum Informationen erhältlich. Jedoch wirdderen hoher Stellenwert für den Organismus durch die starkenOssifikationsdefekte und Wachstumsretardierung verdeutlicht, die bei Patientenmit peroxisomalen Biogenesestörungen oder entsprechenden Knockout-Mausmodellen auftreten. Deshalb wurde im ersten Teil dieser Dissertation dasperoxisomale Kompartiment in unterschiedlichen Zelltypen von Knorpel undKnochen mithilfe einer großen Auswahl morphologischer, biochemischer undmolekularbiologischer Methoden charakterisiert. Im zweiten Teil der Dissertationwurden die pathologischen Konsequenzen einer Peroxisomendysfunktion und diemolekulare Pathogenese der Ossifikationsdefekte in PEX11beta-Knockoutmäusenuntersucht.Die Resultate dieser Dissertation erbrachten den Nachweis von Peroxisomen inallen Zelltypen des Stützgewebes, jedoch mit unterschiedlicher numerischerDichte und heterogener Enzymzusammensetzung der Organellen. Dasperoxisomale Biogeneseprotein Pex14p stellte sich als bester Marker für dieIdentifikation der gesamte Peroxisomenpopulation unterschiedlicher Zelltypenheraus, während die metabolischen Proteine Katalase und der LipidtransporterABCD3 sehr stark in hypertrophischen Knorpelzellen und in Osteoblastenangereichert waren, was eine enge Beziehung zu Ossifikationsprozessennahelegte. In primären Osteoblastenkulturen wurde im Frühstadium (3 Tage)eine geringe numerische Dichte der Peroxisomen nachgewiesen, während einewesentlich höhere Anzahl dieser Organellen in mehr maturen Osteoblasten zuspäteren Zeitpunkten aufgefunden wurden (7d, 11d, 15d). Im Unterschied zuder Peroxisomenverteilung erreichten die Proteinmengen für Katalase und 3-Ketoacyl-CoA-Thiolase, die in drei Tage alten Osteoblasten auch nur in geringerMenge vorhanden waren, ihr Maximum nach 7 Tagen und fielen danach wiederab. Interessanterweise wurden unterschiedliche Mitglieder der PPAR-Familie(Peroxisomenproliferator-aktivierten Rezeptoren alpha, beta;, gamma, Transkriptionsfaktorenfür peroxisomale beta-Oxidationsgene, individuell in unterschiedlicher Weise imVerlauf der Osteoblastendifferenzierung verändert. PPARalpha wurde in ähnlicherWeise wie die metabolischen peroxisomalen Proteine verändert, während dieExpression der mRNA für PPARgamma eine gegensätzliche Regulation aufwies und diefür PPARbeta nicht verändert wurde. Aktivierung von PPARalpha durch Behandlungprimärer Osteoblasten für 6 Tage mit Ciprofibrat führte zur Erhöhung sowohl derPeroxisomenanzahl als auch der metabolischen Enzyme, während Behandlungmit dem PPARgamma-Agonisten Troglitazon nur eine signifikante Veränderungmetabolischer Enzyme bewirkte. Interessanterweise wurden Thiolase und ABCD3durch die PPARalpha-oder PPARgamma-Agonisten in gegensätzlicher Weise verändert, wasvermuten lässt, dass verschiedene PPARs unterschiedliche Wirkung auf dieRegulation peroxisomaler Gene ausüben. Analysen von PEX11beta-Knockoutmäusenmittels flat-panel volumetric CT oder Skelettfärbungen erbrachten eine starkeVerminderung des Volumens, der Masse und der Dichte der Knochen imVergleich zu Kontrolltieren. Vergleichende Analysen der Stützgewebe und vonprimären Osteoblastenkulturen erbrachten eine signifikante Abnahme in derSynthese von osteoblastenspezifischen sekretorischen Markerproteinen(Osteopontin und Osteocalcin) und eine starke Retardierung der verschiedenenOssifikationsprozesse. Weiterhin wurden oxidativer Stress und schwereVeränderungen von osteoblastenspezifischer Signaltransduktionswege in PEX11beta-/--Osteoblasten nachgewiesen. Die Erhöhung der PPARgamma mRNA-Expression wurdegezeigt und die Verminderung des kanonischen Wnt-Signalweges sowie dieTranslokation von Runx2 aus dem Zellkern ins Cytoplasma nachgewiesen.Zusätzlich wurde eine Reduktion der Proteinmenge des FoxO1-Transkriptionsfaktors nachgewiesen, was zusammen mit den oben erwähntenBefunden zu einer Minderung der Ossifikationprozesse in peroxisomalenKrankheiten beitragen könnte.Zusammenfassend lässt sich feststellen, dass reguläre peroxisomaleStoffwechselfunktionen für den normalen Ablauf desmaler und enchondralerOssifikationsprozesse notwendig sind und sowohl für den Schutz derOsteoblasten gegen ROS- und Lipidtoxizität als auch zur Kontrolle der PPARLigandenhomöostaseunerlässlich sind.
Die Rolle der Peroxisome in der Physiologie und Pathologie der Ossifikation und des Knochenstoffwechsels
Keywords: ddc:610